DOES GREEN TEA ENHANCE THE EFFECTS OF PHYSICAL TRAINING ON HEART RATE VARIABILITY? - Santos,Wellington Lourenço Mendes dos (2022)
ABSTRACT Introduction: Green tea is associated with a series of health benefits, as is physical training. However, in combination they present little known chronotropic and autonomic cardiac effects. Objective: To evaluate the effect of the association of chronic administration of green tea and physical training on basal heart rate (HR) and heart rate variability (HRV) in Wistar rats. Methods: Forty-three Wistar rats (Rattus norvegicus, var. albinus), paired by weight and age, were distributed among four experimental groups, titled sedentary control (CONsed, n = 10), trained control (CONtre, n = 08), sedentary tea (CHÁsed, n = 16) and trained tea (CHÁtre, n = 09). Ingestion of the tea was ad libitum. The physical training protocol lasted for eight weeks and consisted of sessions of swimming with incremental loads. At the end of the training, basal heart rate and heart rate variability (HRV) in both time and frequency domains were determined. The level of significance adopted was 5% (p < 0.05). Results: Both physical training and consumption of green tea caused higher resting bradycardia than that of the CONsed group animals. Regarding HRV, the CONtre, CHÁsed, and CHÁtre groups presented significantly higher values than the CONsed group. Supplementation with green tea caused an increase in the variance, high frequency (HF) component, and sympathovagal balance as compared to the CONsed group. Physical training (PT) did not enhance any of the parameters evaluated. Conclusions: There was no significant optimization of the hemodynamic or autonomic cardiovascular parameters resulting from the association between the administration of green tea and physical training in Wistar rats. Level of Evidence IV; Case Series.